Upsurge of Dengue Prevalence During the Third Wave of COVID-19 Pandemic in Bangladesh: Pouring Gasoline to Fire - Fahad Imtiaz Rahman; Sadia Afruz Ether; Md. Rabiul Islam (SAGE Publishing, 2022)
Recently, there has been an alarming increase in Coronavirus Disease-2019 (COVID-19) and dengue virus infection cases in Bangladesh. As the 2 viral diseases share many similar symptoms, healthcare practitioners are facing difficulty in correctly diagnosing them. Even with the help of confirmatory diagnostic tests, the misdiagnosis has been reported in several countries and cases of co-infections are also emerging. This study presents the clinical symptoms of dengue fever and COVID-19 and identifies the overlapping symptoms seen in these 2 diseases that might cause difficulty in diagnosis. We have also discussed cases of misdiagnosis and incidences of co-infection seen in other countries. Finally, we present our recommendations for preventing the surge of dengue and possible solutions for differentiating and managing these 2 diseases. Immediate measures are required from health practitioners and public health policymakers before these viral diseases spiral out of control.